Efeito do laser na resistência de união de cimentos endodônticos: uma revisão sistemática e meta-análise - Ribeiro, Carlos Eduardo Victor da Costa (2019)
Different alternatives of dentine pretreatment have been proposed to improve the adhesion of endodontic sealers to the root canal walls. This study systematically reviewed the scientific literature to summarize the effect of laser on the bond strength of endodontic sealers. Search strategies were conducted in four electronic databases: PubMed/MEDLINE, EMBASE, Scopus and ISI Web of Science. In vitro studies assessing the bond strength of endodontic sealers and comparing the use (intervention) or not (control) of laser were included. The selected studies were submitted to full-text analysis and risk of bias assessment by two reviewers. Meta-analysis was performed in subgroups, considering different types of laser, endodontic sealer and control group. A total of 883 studies were initially identified, wich 11 were included in this review. Standardized mean differences were favorable to laser groups (P<0.05) when it was used: Nd:YAG before epoxy resin-based sealers (vs. EDTAC); diode before epoxy and methacrylate resin-based sealers (vs. no treatment); Er:YAG before calcium silicate-based (vs. no treatment or calcium hydroxide solution); calcium hydroxide-based (vs. no treatment); epoxy resin-based (vs. sodium hypochlorite, no treatment, calcium hydroxide solution or EDTAC); or methacrylate resin-based sealers (vs. calcium hydroxide solution); or Er,Cr:YSGG before epoxy resin-based (vs. no treatment, sodium hypochlorite or EDTAC); or methacrylate-based selaers (vs. no treatment). When a MTA-based sealer was evaluated, diode laser showed the same behaviour of control (plasma or no treatment). When EDTA or citric acid was applied as control, none of the lasers favoured the bond strength of any of the tested sealers. There was great heterogeneity among studies in the meta-analysis and most of them (10 out of 11) presented high risk of bias. In conclusion, high-power lasers may have a beneficial effect on the bond strength of different endodontic sealers, but show no advantages over some conventional chelating agents (EDTA and citric acid). The heterogeneity among studies and their high risk of bias impair definitive conclusions. Thus, further well-designed studies with standardized laser protocols are required to better predict the effect of laser irradiation on root dentine.